(untitled) (Journal of Medical & Health Sciences Review, 2025)
Hyperkalemia, or elevated potassium levels in the blood, is a potential risk for individuals with Type 2 Diabetes (T2D), particularly those on certain classes of medications. Sodium-glucose co-transporter-2 (SGLT-2) inhibitors, glucagon-like peptide-1 (GLP-1) receptor agonists, and dipeptidyl peptidase-4 (DPP-4) inhibitors are widely prescribed for managing T2D. Although these therapies offer substantial benefits in terms of glycemic control, weight management, and cardiovascular protection, concerns regarding their role in electrolyte disturbances, especially hyperkalemia, have emerged. This focused review examines the safety signals for hyperkalemia associated with SGLT-2 inhibitors, GLP-1 receptor agonists, and DPP-4 inhibitors in T2D treatment. The review synthesizes current evidence from clinical trials, observational studies, and post-market surveillance to assess the risk of hyperkalemia and the mechanisms underlying this adverse effect, with a particular focus on renal function and potassium homeostasis. The article aims to provide clinicians with a detailed understanding of the safety profiles of these drug classes, offer guidance on monitoring strategies, and explore the need for additional research in this area.